Clean Water Availability and Access to Health Services on Maternal and Child Health Status - Mahmud, Ratna; Aslinda, Aslinda; Samiun, Zulfia; Mustary, Musliha; Kai, Febriyanti; Surianti, Surianti (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Poor nutrition during pregnancy and childhood is a bad consequence. Stunting children will never reach their peak height or have the best brain development. These children start their lives poorly; they have trouble learning in school, earn less than adults, and face obstacles to being a part of society. This research is to see the relationship between the availability of clean water and access to health services on the health status of mothers and children. This research is quantitative research using analytical observation methods with a "Cross Sectional" approach. Sampling was taken using Cluster Random Sampling with the Chi-Square statistical correlative test with a significance level of 0,05 using SPSS 24. There is a relationship between the availability of clean water and the health status of mothers and children (p-value=0,000), while access to health services does not have a significant relationship with the health status of mothers and children (p-value=0,904). The availability of clean water shows good health status for mothers and children, while access to health services does not have a significant relationship.